Terra Preta (Black Earths) - Spokas, Kurt; Marques, Jose [UNESP]; La Scala, Newton [UNESP]; Nater, Ed; Siqueira, Diego S. [UNESP]; Lal, R. (Crc Press-taylor & Francis Group, 2017)
Fertile dark-colored soils in the Amazon (anthropogenic dark earths or terra preta de Indio) have been attached to historic anthropogenic soil modification through black carbon and other organic amendments from both agricultural and waste management activities of ancient Amazonian natives. This hypothesis was supported by the presence of artifacts (e.g., ceramic pieces) located within these soils and by the assumption that these deposits were unique to the Amazon region. This model of terra preta development has fueled the renaissance into recreating bolstered soil fertility through intentional black carbon additions.